The critic - May, Peter, 1951- (May, Peter, 1951- Enzo files., 2016)
Gaillac, south-west France: Gil Petty, America's most celebrated wine critic, is found strung up in a vineyard, dressed in the ceremonial robes of the Order of the Divine Bottle and pickled in wine. For forensic expert Enzo Macleod, the key to this unsolved murder lies in decoding Petty's mysterious reviews - which could make or break a vineyard's reputation. Enzo finds that beneath the tranquil facade of French viticulture lurks a back-stabbing community riddled with rivalry - and someone who is ready to stop him, even if they have to kill again...